Indonesia-Malaysia Relations: From Confrontation to Normalization (1963–1967) - Ririn Darini; Hanafi Hussin; Ajat Sudrajat; Ita Mutiara Dewi; Danar Widiyanta; Sekar Ayu Asmara; Shofi Sani (Indonesian Historical Studies, 2025)
This study examines the evolution of Indonesia-Malaysia relations during the confrontation and normalization phase from 1963 to 1967, employing historical analysis. Initially characterized by collaboration after Malaysia gained independence in 1957, the bilateral ties worsened between 1961 and 1965 due to conflicts and hostilities. The study emphasizes significant elements of Indonesia's confrontation strategy, such as the Dwikora policy, which aimed to bolster the Indonesian revolution and support revolutionary activities in Malaya, Sabah, Sarawak, and Brunei. It also examines the enforcement of Komando Operasi Tertinggi (KOTI) Order No. 1 of 1963, which severed economic and trade ties with Singapore and Malaysia, and Indonesia's 1965 decision to exit the United Nations. Additionally, the research outlines the conflict's resolution, highlighted by the 1966 Bangkok conference where both nations agreed to restore relations, followed by Indonesia's return to the United Nations later that year. These insights enhance the comprehension of the political and diplomatic transformations influencing Southeast Asian interstate relations during this pivotal era.